PERAN ORANGTUA DALAM PENANGANAN STUNTING (Studi di: Kecamatan Lima Puluh, Kota Pekanbaru) - Krishayati Fauji Rahayu; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted in Kecamatan Lima Puluh, Pekanbaru. The objectives of this study were to determine: 1) Parents' knowledge of the causes of stunting problems; 2) The role and efforts of parents in handling stunting in Lima Puluh Kota Pekanbaru. This research uses a descriptive quantitative method. The population in this study were parents of children experiencing stunting in Lima Puluh , Pekanbaru,the population in this study  amounted to 170 and the sample in this study was 63 respondents. Sampling using simple random sampling techniques The data instruments are observations, questionnaires, and documentation. Based on the results of the study, it can be concluded that the level of parental knowledge of stunting in Lima Puluh, Pekanbaru city is classified as high with a frequency of 52 respondents (82.5%) while parents with a moderate level of knowledge category are 11 respondents (11%). parents' efforts in handling stunting in Lima Puluh, Pekanbaru. A total of 62 respondents from 63 respondents (98.4%) met the nutritional and vitamin adequacy of toddlers, of these 63 respondents (100%) answered giving additional fruit and vegetables, 5 respondents (7.9%) answered not to consume while 58 respondents (92, 1%) answered consuming vitamin A, that 63 respondents (100%) gave immunizations to children. 56 respondents (88.9%) gave breastfeeding and complementary foods, 60 respondents (95.2%) did not improve sanitation at home, while 3 of 63 respondents (4.8%) improved sanitation at home after knowing that sanitation was what affects Stunting.  Keywords: Role, Parents, Handling, Stunting